Factors Associated With an Increased Risk of Instrumental Vaginal Delivery in Women With Epidural Analgesia for Labor: A Retrospective Cohort Study. Issue 3 (24th September 2022) - Au-Yong, P.S.; Tan, C.W.; Tan, W.H.; Tan, K.H.; Goh, Z.; Sultana, R.; Sng, B.L.
Abstract : ( Eur J Anaesthesiol . 2021;38:1059–1066) Although epidural analgesia is an effective and common method of pain management during labor and delivery, studies suggest there may be an increased risk of instrumental vaginal delivery (IVD, forceps or vacuum extractor) use. Instrumental delivery increases risk of maternal and neonatal morbidity and outcomes. This study aimed to identify women at increased risk of instrumental delivery and strategies to decrease associated maternal and neonatal morbidity.